Risk Management for 4-H Youth Development Work: Records and Contracts - Dale Pracht; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS)
4H10.4, a 2-page fact sheet by Dale Pracht, Marilyn Norman, Kate Fogarty, and Jean Hink, is part of the Risk Management for 4-H Youth Development Work series. It discusses the risks involved with contracts, public records and other paperwork. Includes references. Published by the Florida 4-H Youth Development Program, August 2010.